Association of Optic Neuritis with CYP4F2 Gene Single Nucleotide Polymorphism and IL-17A Concentration - Mantas Banevicius; Alvita Vilkeviciute; Brigita Glebauskiene; Loresa Kriauciuniene; Rasa Liutkeviciene (Journal of Ophthalmology)
Background. The aetiology and pathophysiology of optic neuritis (ON) is not absolutely clear but genetic and inflammatory factors may be also involved in its development. The aim of the present study was to determine the influence of single nucleotide polymorphism (SNP) of CYP4F2 (rs1558139) and serum levels of IL-17A on ON development. Materials and Methods. Forty patients with ON and 164 control subjects were evaluated. Patients were divided by gender, also ON patients were divided into two subgroups: ON with and without multiple sclerosis (MS). CYP4F2 rs1558139 was genotyped using real-time PCR. Serum IL-17A levels were measured using ELISA IL-17A kits. Results. We found that A/A genotype of CYP4F2 rs1558139 was statistically significantly more frequent in men with ON and MS than in women: 57.1% versus 0%, p=0.009. Also, allele A was statistically significantly more frequent in men with ON and MS than in women: 71.4% versus 37.5%, p=0.044. Serum levels of IL-17A were higher in ON group than in control group: (median, IQR): 20.55 pg/ml, 30.66 pg/ml versus 8.97 pg/ml, 6.24 pg/ml, p<0.001. Conclusion. The higher IL-17A levels were found to be associated with ON, while allele A at rs1558139 was associated only with ON with MS in male patients.